Pengaruh Perilaku Pengguna Teknologi Informasi dan Kualitas Teknologi Informasi Terhadap Loyalitas Pelanggan Warnet Ditengah Ancaman Perkembangan Teknologi Informasi Pesaing - amrizal amrizal (Computer Based Information System Journal, 2014)
The development of information technology has brought changes for humans to meet their needs. If any of the technology has been used, then a new technology so the old technology will gradually be abandoned by the user, this will require technology investments that have been incurred should be able to adjust to existing conditions or changes in the function and purpose of existence so as to keep the business going amid threats tenologi competitors. There are two things that need to be maintained in achieving organizational resilience to increase customer loyalty and technology in order to keep using the service, namely the behavior of the users of information technology and information technology quality, so however the development of competing technologies, but remain loyal customers using these technologies. Customer loyalty is done by a level of customer loyalty based on the comparison between the perceived outcome desired expectations.